DUAL CAREER MODEL FOR LATVIA’S ENVIRONMENT - Amantova, Ingrida; Abele, Agita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Combining the systems of high-performance sport and the general education on the high school level is a research object in sports science since the 1980s (Teubert, 2009). While a large number of scientists have studied the dual overload of athletes/students in school and high-performance sport, only a few have focused on the coordination or collaboration of these two structures - school and high-performance sport (Teubert, 2009). Therefore, in this study will be research the Murjani Sports Gymasium (MSG) as the only specialized sports education institution in Latvia which provides high school education and simultaneously the realisation of high-performance sports career. Furthermore, the aim of this study is to develop a dual career model for Latvia’s socio-economic environment. Additional to the literature research and review of national and European regulations, an online survey was carried out. MSG teachers and coaches were invited to complete voluntary an online survey, a questionnaire related to theoretical issues. Overall, 32 persons completed the questionnaire. MSG teachers and coaches were asked to evaluate the dual career system in MSG and to give suggestions for development which has significant meaning in dual career system improvement and development in the Latvian sports industry. The data were analysed with the statistical analysis by using IBM SPSS 21.0 software: a) quantitative descriptive statistics; b) correlation analysis. Furthermore, the induction or cognition method as qualitative research method were used to draw conclusions and establish a dual career model for Latvia's socio-economic environment.